Factores familiares que inciden en la ideación suicida de los adolescentes entre 12- 14 años de una institución educativa de Riohacha. (2023)
Good family functioning contributes to the mental health of adolescents and acts as a protective factor against the difficult situations they face and overcome. Therefore, the function of a house is perhaps one of the most discussed aspects. The purpose of the study was to know the family factors that affect suicidal ideation in adolescents between 12 and 14 years of age at the José Antonio Galán educational institution in Riohacha. To achieve these objectives, quantitative and descriptive methodological elements will be used, so the Beck Hopelessness Scale and the Family Apgar will be used to describe the influence of family factors on suicidal ideation in adolescents from the educational institution studied,